Neural signatures of prioritization and facilitation in retrieving repeated items in visual working memory - Narvaria, Abhishek Singh; Banerjee, Arpan; Roy, Dipanjan (Frontiers in Human Neuroscience, 2025)
Visual working memory (VWM) is a limited-capacity system where working memory items compete for retrieval. Some items are maintained in the working memory in the “region of direct access,” which holds information readily available for processing, while other items are in a passive or activated long-term memory state and require cognitive control. Moreover, their recognition requires moving from the most active template in VWM to another one with the shift of attention. Stimulus properties based on similarity can link items together, which can facilitate their retrieval due to prioritization. To investigate the neural dynamics of differential processing of repeated versus not-repeated items in working memory, we designed a modified Sternberg task for testing recognition in a VWM-based EEG study where human participants respond to a probe for an item’s presence or absence in the representation of an encoded memory array containing repeated and not repeated items. Significantly slower response times and comparatively poor accuracy for recognizing not-repeated items suggest that they are not prioritized. We identified specific differences in spectral perturbations for sensor clusters in the power of different frequency bands as the neural correlate of probe matching for not-repeated vs. repeated conditions, reflecting biased access to VWM items. For not-repeated item probe matching, delay in beta desynchronization suggests poor memory-guided action selection behavior. An increase in frontal theta and parietal alpha power demonstrated a demand for stronger cognitive control for retrieving items for not-repeated probe matching by shielding them from distracting repeated items. In summary, our study provides crucial empirical evidence of facilitation and prioritization of repeated items over non-repeated items and explains the probable role of different EEG rhythms in facilitated recognition of repeated items over goal-relevant, not-repeated items in VWM.